2020
DOI: 10.18510/hssr.2020.81103
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Building Communication and Negotiation Competencies for Prospective Accountants

Abstract: Purpose of the study: The objective of the study is to evaluate the effectiveness of the existing strategies employed by the department of accounting in equipping its students with communication and negotiation competencies (CNC). Classroom, extracurricular, and internship are the main strategies to build students' CNC. This study aims to identify the impacts of classroom learning, extra-curricular activities, internship and community service on CNC. Methodology:The study employs a quantitative approach by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Yanto et al (2018) stated that students need to improve communication and training skills as essential competencies that will be useful for graduates at work, especially when facing differences of opinion and perceptions with colleagues. The findings of Yanto et al (2020) have also confirmed that students' communication skills shown from involvement have a positive and significant effect on negotiation skills, so collaborative processes in online learning may train communication and negotiation skills both with lecturers and other students in class. In the learning process, students must achieve learning objectives covering three domains, i.e., cognitive, affective, and psychomotor.…”
Section: Rise-international Journal Of Sociology Ofmentioning
confidence: 55%
“…Yanto et al (2018) stated that students need to improve communication and training skills as essential competencies that will be useful for graduates at work, especially when facing differences of opinion and perceptions with colleagues. The findings of Yanto et al (2020) have also confirmed that students' communication skills shown from involvement have a positive and significant effect on negotiation skills, so collaborative processes in online learning may train communication and negotiation skills both with lecturers and other students in class. In the learning process, students must achieve learning objectives covering three domains, i.e., cognitive, affective, and psychomotor.…”
Section: Rise-international Journal Of Sociology Ofmentioning
confidence: 55%